Fragile X mental retardation protein‐regulated proinflammatory cytokine expression in the spinal cord contributes to the pathogenesis of inflammatory pain induced by complete Freund's adjuvant. Issue 3 (29th August 2021) - Yang, Yixin; Zhao, Jinsong; Li, Yunze; Li, Xiangyao; Chen, Xiaowei; Feng, Zhiying
Abstract: Studies have verified that Fragile X mental retardation protein (FMRP), an RNA‐binding protein, plays a potential role in the pathogenesis of formalin‐ and (RS)‐3, 5‐dihydroxyphenylglycine‐induced abnormal pain sensations. However, the role of FMRP in inflammatory pain has not been reported. Here, we showed an increase in FMRP expression in the spinal dorsal horn (SDH) in a rat model of inflammatory pain induced by complete Freund's adjuvant (CFA). Double immunofluorescence staining revealed that FMRP was mainly expressed in spinal neurons and colocalized with proinflammatory cytokines [tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6)]. After consecutive intrathecal injection of fragile X mental retardation 1 small interfering RNA for 3 days post‐CFA injection, FMRP expression in the SDH was reduced, and CFA‐induced hyperalgesia was decreased. In addition, the CFA‐induced increase in spinal TNF‐α and IL‐6 production was significantly suppressed by intrathecal administration of fragile X mental retardation 1 small interfering RNA. Together, these results suggest that FMRP regulates TNF‐α and IL‐6 levels in the SDH and plays an important role in inflammatory pain. Abstract : Fragile X mental retardation protein (FMRP), an RNA‐binding protein, plays a potential role in the pathogenesis of formalin‐ and (RS)‐3, 5‐dihydroxyphenylglycine‐induced abnormal pain sensations. However, the involvement of spinal FMRP in inflammatory pain has not been explored. Here, we show that FMRP was mainly expressed in spinal neurons and colocalized with tumor necrosis factor‐α and interleukin‐6. And FMRP contributes to inflammatory pain induced by complete Freund's adjuvant through the modulation of tumor necrosis factor‐α and interleukin‐6 expression in the spinal dorsal horn. These findings suggest that FMRP in the dorsal horn could be a potential therapeutic target for inflammatory pain.